2013
DOI: 10.1002/hipo.22149
|View full text |Cite
|
Sign up to set email alerts
|

Memory reconsolidation allows the consolidation of a concomitant weak learning through a synaptic tagging and capture mechanism

Abstract: Motivated by the synaptic tagging and capture (STC) hypothesis, it was recently shown that a weak learning, only able to produce short-term memory (STM), can succeed in establishing long-term memory (LTM) with a concomitant, stronger experience. This is consistent with the capture, by the first-tagged event, of the so-called plasticity-related proteins (PRPs) provided by the second one. Here, we describe how a concomitant session of reactivation/reconsolidation of a stronger, contextual fear conditioning (CFC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 39 publications
(73 reference statements)
1
23
1
Order By: Relevance
“…The increased connectivity between the hand region and regions hypothetically involved in the declarative memory of the sequence in the present study might reflect the action of mechanisms by which the salience of these memories leads to their selection for subsequent sleep-dependent consolidation (Stickgold and Walker, 2013). While the actual mechanisms underlying the assignment of salience and selection are unknown, animal studies propose that memories are selected and sustained for system level consolidation in neocortical networks by ‘synaptic tagging’ in the immediate aftermath of learning (Cassini et al, 2013; Frey and Morris, 1997; Redondo and Morris, 2011). …”
Section: 0 Discussionmentioning
confidence: 99%
“…The increased connectivity between the hand region and regions hypothetically involved in the declarative memory of the sequence in the present study might reflect the action of mechanisms by which the salience of these memories leads to their selection for subsequent sleep-dependent consolidation (Stickgold and Walker, 2013). While the actual mechanisms underlying the assignment of salience and selection are unknown, animal studies propose that memories are selected and sustained for system level consolidation in neocortical networks by ‘synaptic tagging’ in the immediate aftermath of learning (Cassini et al, 2013; Frey and Morris, 1997; Redondo and Morris, 2011). …”
Section: 0 Discussionmentioning
confidence: 99%
“…This means that, to establish a lasting memory, at least two parallel and complementary processes should occur: the setting of a mark (the learning tag -LT-) induced by the learning, that will determine that this information is plausible to be stored and where to do it; and the synthesis of Plasticity Related Proteins (PRPs) that once captured at the tagged sites will allow memory consolidation (Moncada & Viola, 2007). This process, named behavioral tagging (BT), was observed underlying the formation of aversive, non-aversive, contextual, spatial, taste-recognition, hippocampus and cortex-dependent longterm memories, as well as long-term extinction of the contextual fear memory (Almaguer-Melian et al, 2012;Ballarini et al, 2009;Cassini et al, 2013;de Carvalho Myskiw et al, 2013;Lu et al, 2011;Moncada & Viola, 2007;Wang et al, 2007); transforming it into a strong candidate for a general mechanism of LTM formation. Thus, understanding the mechanisms and structures responsible for setting the LTs as well as identifying the mechanisms and structures that regulate the synthesis of PRPs, results essential for a deeper comprehension of how learning and memory processing occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Different novel experiences, such as the exploration of novel arenas or novel objects and tasting novel flavors, have been used to provide the PRPs required for the consolidation of hippocampus-or cortex-dependent tasks such as the inhibitory avoidance (IA), spatial object recognition (SOR), contextual fear conditioning, taste aversion and event arena (Ballarini et al, 2009;Dong et al, 2012;Lu et al, 2011;Moncada & Viola, 2007;Wang et al, 2010). Indeed, contextual fear and water maze tasks could also promote the hippocampus dependent SOR memory (Cassini et al, 2013). However, not only behavioral treatments have been effective in providing PRPs for memory consolidation, but also the systemic injection of the dopaminergic and adrenergic agonists SKF3393 and dobutamine have been shown induce the synthesis of those PRPs required to consolidate the IA memory in the hippocampus (Moncada et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In parallel with our aim of examining whether other events can modulate memory persistence, it has recently been shown that the reconsolidation of contextual fear conditioning and place memory in the water maze can each help make an otherwise weak object-location memory last for 24 h (Cassini et al 2013). These findings further expand the generality of the phenomenon.…”
Section: Behavioral Interpretationmentioning
confidence: 99%
“…This type of manipulation is possible in animal studies because prospective studies can be done. Rat studies reported that exploration of a novel box, or other novel events, could enhance memory in various hippocampusdependent tasks when given 15 min (Almaguer-Melian et al 2012), 30 min , or 1 h (Cassini et al 2013;de Carvalho Myskiw et al 2013) after encoding.…”
Section: Behavioral Interpretationmentioning
confidence: 99%